The Right to Have Places of Worship: The Cemevi Case in Turkey - Omur Aydin; Bulut Gurpinar (Religions, 2022)
This study discusses the obligation of the state to provide places of worship to religious communities in society, or to grant such existing places a specific status in law and thus entitle them to benefit from some public privileges. The study finds that international human rights law does not impose direct positive obligations on the state in this context. If, however, a state has granted such public privileges and statuses to some religious communities in the society, or has developed a concordat-type relationship with them, then it should base this differential treatment between religious communities on objective and reasonable justifications. Cemevis, which Alevis accept as their places of worship, do not have the status of a place of worship in Turkey. In the official discourse, the difference between Alevism and Sunnism is approached from a cultural, not religious, perspective. The study determines that practices of secularism in Turkey have atypical appearances in some issues. There is an implicit concordat relationship between the state and the Sunni/Hanafi community, although this is not expressed in the official discourse, and Turkish-style secularism is reluctant to formalize this relationship or to establish similar concordat-type relationships with other religious communities. Due to this preference, Alevis cannot reach the status of a recognized religious society in Turkey, and cemevis cannot be granted the status of places of worship that are entitled to benefit from public privileges.